Estudio de factibilidad para la creación de una APP móvil que permita la consulta de ruta, frecuencias y precios de la Cooperativa de Trasporte Interprovincial Caluma del Cantón Caluma en la Provincia de Bolívar - Jimenez Balseca, Guissela María (2020)
Mobile applications on a day-to-day basis are a tool that keep everyone connected and informed in all parts of the world, such is the case that in the city of Caluma it is intended to study the feasibility of creating a mobile app that allows the consultation of the route, frequencies and prices of the Caluma Interprovincial Transport Cooperative of the Caluma canton in the province of Bolívar. The line of research in which the case study will be framed is Information and communication systems, entrepreneurship and innovation with its respective subline in networks and intelligent software and hardware technologies. The technique to be used will be the formulation of questions or survey, as an instrument the questionnaire that using TypeForm an online tool that allows creating surveys, analyzing and monitoring the results. The methodology that will be used is qualitative and we will be working with the deductive method; as well as the bibliographic material because it supports the present research work, limiting this research work only to the feasibility study, but not to the development or implementation of the software. As results, the way in which the present case study is competitively beneficial with other companies due to the easy access and management of information that a mobile application can provide will be evidenced.